1976
DOI: 10.1159/000180754
|View full text |Cite
|
Sign up to set email alerts
|

Renal Acidification in Patients with Mineralocorticoid Deficiency

Abstract: Renal acidification was studied in eight patients with Addison’s disease or bilateral adrenalectomy receiving glucocorticoid replacement only and without renal insufficiency (group I); in five patients with hyporeninemic hypoaldosteronism and moderate chronic renal insufficiency (group II), and in nine control subjects (group III). During acidosis minimal urine pH was 5.4 or less in all subjects, but excretion of ammonium and titratable acid was moderately reduced in group I and markedly reduced in group II. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…are similar to those reported by other authors [7,[9][10][11][12]. In this group we observed a close inverse expo nential correlation between urinary sodium levels and PRA (r = 0.908; p < 0.001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…are similar to those reported by other authors [7,[9][10][11][12]. In this group we observed a close inverse expo nential correlation between urinary sodium levels and PRA (r = 0.908; p < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…4) (r = 0.588; p < 0.05), both under basal conditions and after a NH4C1 overload. This correlation is similar to that described in other alterations in renal acidification [12,60,61], in which the decrease in NH4 secretion leads to an alkalinization of the urine. Di Telia et al [53], working with adrenalectomized rats subjected to an NH4C1 overload, reported results consistent with our own.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, effective circulating volume depletion could also have played a role in the significant increase in serum potassium concentration [4], Even though scrum chloride levels were within normal limits, a relative hyperchlor emia (serum NaVCF = 1.33) was apparent. The presence of hyperchloremic metabolic acidosis in our patient was probably the result of (a) a loss of aldosterone effect at the outer medullary collecting duct, (b) a dimin ished phosphate excretion from lack of glu cocorticoid and (c) a depression of ammoniagenesis by hyperkalemia [5][6][7], Finally, hypercalcemia was also present in our pa tient, possibly owing to adrenal insufficiency [ 8],…”
mentioning
confidence: 50%
“…In addition to hypoaldosteronism, a reduction in the number of nephrons would be ex pected to amplify a reduction in net acid excretion by limiting renal ammonia production and by impairing bicarbonate reabsorption [13,14].…”
Section: Discussionmentioning
confidence: 99%